Formulasi dan Uji Kestabilan Fisik Suspensi Topikal yang Mengandung Ekstrak Nerii Folium sebagai Antibakteri dalam Sediaan Anti Jerawat - Djajadisastra, Joshita; Munim, Abdul; Hidayah, Octaviarini (Majalah Ilmu Kefarmasian, 2007)
Nerium oleander is one of the plants that can be developed to be a herbal medicine because the leaf extract has an antibacterial activity against some microorganisms and empirically had been used to solve the acne problem. The anti acne formulation should not make the acne worse because of mistaken to choose the dosage form. The suspension dosage form (has no oil content makes the acne worse) containing the dried leaf extract of Nerium oleander in 97% alcohol was chosen to be formulated by varying respectively carbomer, sodium carboxy methyl cellulose and tragacanth as a suspending agent. The concentration of Nerii folium extract in the suspension was based on the Minimal Inhibitory Concentration of the extract against Propionibacterium acnes and Staphylococcus. The evaluation of the formula was done by physical stability test including organoleptic test (color and odor), pH, volume of sedimentation, mean particle diameter size, viscosity stored in low temperature of 4oC, room tperature of 28oC, and high temperature of 40oC, cycling test and mechanical test.The results showed that suspension with sodium carboxy methyl cellulose as the suspending agent has better physical stability than carbomer or tragacanth.